2011
DOI: 10.1074/jbc.m110.161810
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-specific Glycoprotein 1 Induces Endothelial Tubulogenesis through Interaction with Cell Surface Proteoglycans

Abstract: Pregnancy-specific ␤1 glycoproteins (PSGs) are the most abundant fetal proteins in the maternal bloodstream in late pregnancy. They are secreted by the syncytiotrophoblast and are detected around day 14 postfertilization. There are 11 human PSG genes, which encode a family of proteins exhibiting significant conservation at the amino acid level. We and others have proposed that PSGs have an immune modulatory function. In addition, we recently postulated that they are proangiogenic due to their ability to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 52 publications
1
57
0
Order By: Relevance
“…We have previously reported that human PSG1 binding to the HS chains of syndecans induces the formation of capillarylike structures by endothelial cells [35,36]. Because PSG22 also binds to syndecans, we hypothesized that this murine PSG might also induce endothelial tube formation.…”
Section: Psg22n1a Induces Capillary Differentiation In Vitromentioning
confidence: 94%
“…We have previously reported that human PSG1 binding to the HS chains of syndecans induces the formation of capillarylike structures by endothelial cells [35,36]. Because PSG22 also binds to syndecans, we hypothesized that this murine PSG might also induce endothelial tube formation.…”
Section: Psg22n1a Induces Capillary Differentiation In Vitromentioning
confidence: 94%
“…PSG9 belongs to the carcinoembryonic antigen family and is a highly glycosylated protein that is deregulated during colorectal carcinogenesis [28]. PSG1 regulates immunoreactions and has proangiogenic properties [29]. Furthermore, PSG9 interacts with AFP and is involved in the TGF-β signaling pathway, based on network analysis ( Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…79 CTB production of numerous isoforms of pregnancy-specific beta-1 glycoprotein (PSG-1) were also upregulated. Although their functions are not well understood, they appear to have vasculogenic 80,81 and immune properties. 82,83 Glypican 3, proposed as a receptor for some PSG family members, 84 was also upregulated.…”
Section: Discussionmentioning
confidence: 96%